Biodiesel from kernel oil of sweet cherry (Prunus avium L.) seed. Issue 17 (1st September 2016) - Demirbas, Ayhan
ABSTRACT: Kernel oil of sweet cherry seed ( Prunus avium L.) was extracted with hexane in a Soxhlet extractor. Sweet cherry kernel oil contains more than 87% unsaturated fatty acids, such as oleic acid (43.7% by weight), linoleic acid (41.8% by weight), and linolenic acid. The biodiesel from kernel oil of sweet cherry seed in itself is not significantly different from biodiesel produced from common vegetable oils.